An Investigation of the Gifted Education Programs and its Effectiveness across the Private Middle Schools in Dubai - SHARMA, NEHA HARESH (2021)
The concept of inclusion remains at the heart of successful education and the UAE follows the rights-based model of inclusion. Gifted education programs are essential to offer academically aligned curriculum and instructional practices, cater to the socio-emotional needs of advanced learners, and provide the skills to advance their careers. This study investigated the gifted programs offered and evaluated its effectiveness in private middle schools in Dubai. Currently, we cannot estimate the number of gifted learners that go unidentified or underserved leading to individual needs being unrecognised. This disheartening situation exists owing to the dearth of prior research in giftedness in the local context. Following the pragmatic paradigm and exploratory sequential mixed methods, the current investigation used the NAFC 2019 PreK-12 gifted education programming standards for guidance alongside appropriate theoretical and conceptual frameworks. Qualitative research including interviews and the document analysis of the KHDA school inspection reports was followed by quantitative analysis of student attainment data in core subjects in the cognitive domain alongside the self-perception data in the affective domain, and concluded with the qualitative analysis of the findings, guided by the giftedness literature. Few suggestions regarding improvements in the gifted programs and recommendations for future research are reported.